(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The production of high-quality composite solid fuels largely depends on the binder. The use of different types of binding materials in the production of composite solid fuels determines the quality and cost of the resulting fuel. The cheapest type of binder is clay. It is rare to use clay as a binder, as it increases the ash content of the fuel and deteriorates the quality characteristics. Chemical and mechanical activation of clay improves the quality characteristics and binding properties of the clay. We have studied and established the optimal oncentration values of one of the types of clay – bentonite in the activated state, which provides the necessary strength of the briquettes, as well as calorific value